2007
DOI: 10.1016/j.virol.2006.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression in CD8+ cells from HIV-1-infected subjects showing suppression of HIV replication

Abstract: CD8(+) cells from healthy HIV-1-infected individuals suppress human immunodeficiency virus (HIV) replication in infected cells by a non-cytotoxic mechanism. This activity is associated with the production of a soluble CD8(+) cell antiviral factor (CAF) that inhibits viral replication at the level of transcription. Strong CD8(+) cell non-cytotoxic anti-HIV responses (CNARs) correlate with an asymptomatic state and long-term survival of HIV-infected individuals. This antiviral activity is lost when the infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 25 publications
4
23
0
Order By: Relevance
“…Uninfected macaques were included to minimize the effects that might potentially be related to long-term SIV-infection and distinguishes this work from previously published experiments in HIV-infected humans (Diaz et al , 2003; Katz et al , 2011; Killian et al , 2013; Martinez-Mariño et al , 2007). Comparison between CNAR(−) versus CNAR(+) animals revealed 143 differentially regulated genes (differential expression over twofold, P <0.1), which belonged to diverse biological processes (Table S1, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uninfected macaques were included to minimize the effects that might potentially be related to long-term SIV-infection and distinguishes this work from previously published experiments in HIV-infected humans (Diaz et al , 2003; Katz et al , 2011; Killian et al , 2013; Martinez-Mariño et al , 2007). Comparison between CNAR(−) versus CNAR(+) animals revealed 143 differentially regulated genes (differential expression over twofold, P <0.1), which belonged to diverse biological processes (Table S1, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The first study involved a pair of HIV-1 discordant identical twins (Diaz et al , 2003). Another study included four CNAR-positive and four CNAR-negative HIV-infected individuals (Martinez-Mariño et al , 2007). There was no overlap between the genes identified in these two reports.…”
Section: Introductionmentioning
confidence: 99%
“…In order to identify correlates of antiviral control, we assessed the expression of a panel of cytokines, including MIP-1␣, MIP-1␣P, MIP-1␤, IFN-␥, XCL1, GM-CSF, RANTES, and TNFRSF9. We and others have shown that IFN-␥ and the ␤-chemokines MIP-1␣ and MIP-1␤ are associated with CD8 ϩ T cell inhibition of HIV-1 (17,42,(44)(45)(46)(47)(48). MIP-1␣, MIP-1␣P, and MIP-1␤ bind CCR5 and block the entry of R5-tropic viruses (including transmitted/founder viruses) in CD4 ϩ T cells (44,49,50).…”
Section: Soluble Hiv-1 Inhibition From P24-and Nef-specific Cd8mentioning
confidence: 96%
“…The antiviral activity of this nuclear protein had been suggested by earlier restriction differentiation analyses studies indicating that TOE1 RNA was expressed at higher levels in cells showing CNAR vs. those that did not (21). This finding, however, was not confirmed by subsequent DNA microarray procedures (22,23). The de Belle research group based their conclusion on TOE1 and CAF from the effect of TOE1 on HIV transcription, its surprising secretion by CD8+ lymphocytes, and its ability to penetrate cells and block HIV replication (17).…”
mentioning
confidence: 90%